Clinical Evidence on Hemodiafiltration: A Systematic Review and a Meta‐analysis. Issue 2 (20th February 2014) - Mostovaya, Ira M.; Blankestijn, Peter J.; Bots, Michiel L.; Covic, Adrian; Davenport, Andrew; Grooteman, Muriel P.C.; Hegbrant, Jörgen; Locatelli, Francesco; Vanholder, Raymond; Nubé, Menso J.; ,
Abstract In this review, a systematic literature search and meta‐analysis were performed to assess the effects of hemodiafiltration (HDF) on clinical outcome, as compared with hemodialysis (HD). Furthermore, the relation between the convection volume in HDF and clinical outcome was studied. The literature search identified six randomized controlled trials (RCTs). In a meta‐analysis of these RCTs, HDF treatment was related to a decreased risk of mortality (RR: 0.84; 95% CI 0.73–0.96) and cardiovascular death (RR: 0.73; 95% CI 0.57–0.92). Post hoc analyses of the three largest RCTs suggested an inverse relation between the magnitude of convection volume and mortality risk. The evidence presented in this analysis supports a wider acceptance of HDF.